Healthy management of menopause: exploring issues and user requirements for mobile intervention / Aznoora Osman, Nur Emieliana Izzatie Ahmad Noraimi and Nadia Abdul Wahab - Osman, Aznoora; Ahmad Noraimi, Nur Emieliana Izzatie; Abdul Wahab, Nadia (UiTM Cawangan Perlis, 2021)
Designing and developing a mobile health intervention that focuses on menopausal symptom management and emotional support for women should be grounded by some knowledge about their problems and needs. Therefore, to gather information about the issues surrounding women in their menopausal phase, review of literatures pertaining to the topic was conducted, followed by a brief preliminary investigation (PI) using online survey method which was administered to Malaysian women for two weeks. The purpose of PI was to examine their awareness about menopause, namely its phases and symptoms management, as well as methods of information searching on menopause. Respondents were also inquired about their requirements from mobile app to support management of menopause. A total of 30 respondents answered the survey, with majority of them were between the ages of 40 and 59 years old. It was discovered that menopausal women had experienced variety of symptoms, some could be intense more often than the others, and they use diary or book to record these symptoms, which is deemed ineffective. It is imperative to help Malaysian women to manage this unavoidable phase of their lives in a more convenient approach. Therefore, a mobile app that supports symptoms management, and provides educational and motivational tips in Malay language is proposed.